2020
DOI: 10.2478/hukin-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Small-Sided Games as an Aerobic Fitness Assessment Supplement within Elite Level Professional Soccer

Abstract: The purpose of this investigation was to quantify the association between 5 vs. 5 small sided games (SSG) running performance and physiological performance during the Yo-YoIR1 test to ascertain the utility of SSGs as a potential fitness test modality within elite professional soccer players. Twenty-three (n = 23) elite male professional soccer players (mean ± SD age 25.3 ± 3.1 yrs, mass: 76 ± 9 kg, height: 176 ± 9 cm) were assessed. Players completed an intermittent aerobic fitness test (Yo-YoIR1) and a 5 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 35 publications
5
57
2
3
Order By: Relevance
“…The large-to-very-large relationships between V IFT and TD measures revealed in the present study are in line with other study that demonstrated a strong association between Yo-Yo IR scores and total distance covered and high-intensity running speeds during match play, suggesting a strong validity ( Aquino et al, 2020 ). In fact, in a study conducted on 23 elite soccer players with the aim to analyze the relationships between a 5v5 SSG and the YYIR1 running performance, it was found that TD during the SSGs was very strongly associated with YYIR1 performance ( r = 0.88; Owen et al, 2020 ). In our study, the final 30-15 IFT score (V IFT ) revealed similar associations with TD ( r range: 0.69; 0.87) during SSG drills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The large-to-very-large relationships between V IFT and TD measures revealed in the present study are in line with other study that demonstrated a strong association between Yo-Yo IR scores and total distance covered and high-intensity running speeds during match play, suggesting a strong validity ( Aquino et al, 2020 ). In fact, in a study conducted on 23 elite soccer players with the aim to analyze the relationships between a 5v5 SSG and the YYIR1 running performance, it was found that TD during the SSGs was very strongly associated with YYIR1 performance ( r = 0.88; Owen et al, 2020 ). In our study, the final 30-15 IFT score (V IFT ) revealed similar associations with TD ( r range: 0.69; 0.87) during SSG drills.…”
Section: Discussionmentioning
confidence: 99%
“…Considering SSGs, moderate-to-large correlations were observed when examining the relationships between external loads during 6v6 drills and YYIR performance ( Stevens et al, 2016 ). Also, moderate-to-very large negative relationships were reported between heart rate measures, such as time spent above 80% HR max (red zone), %HR max , during SSGs and YYIR performance ( Stevens et al, 2016 ; Owen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beberapa penelitian telah menunjukkan bahwa kegiatan olahraga tim seperti sepak bola, bola voli, bola basket, dan bola tangan secara efektif mengurangi tekanan darah (Trajković, et al, 2020). Di era milenial saat ini, sepakbola merupakan cabang olahraga beregu yang diminati dan digemari mulai dari anak-anak, remaja, sampai dewasa (Kristianto, et al, 2020), terlepas dari faktor usia, jenis kelamin dan faktor sosial (Gema, et al, 2016 (Castillo, et al, 2021 (Owen, et al, 2020). (Práxedes, et al, 2018) 19 orang Metode eksperimen dengan instrument GPET SSG memberikan pengaruh terhadap pemain dalam mengambil keputusan dan melakukan keterampilan teknik passing (Reinhardt, et al, 2020) 18 (Perdana, et al, 2017) 24 (Hammami, et al, 2018…”
Section: Pendahuluanunclassified